2020
DOI: 10.30607/kvj.728554
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Milk Fatty Acid Profile and Expression Levels of Scd, Fasn and Srebpf1 Genes in Damascus Dairy Goats

Abstract: In this study, the relationship between the expression levels of SCD, FASN, SREBPF1 genes and milk fatty acid profiles in goat milks with low (LSFA) and high (HSFA) saturated fatty acid content was investigated and correlated. In HSFA group, SCD, FASN and SREBPF1 genes were approximately 7, 9 and 4 folds more expressed than LSFA in milk somatic cells, respectively (P<0.01). Also, positive correlations were determined between SCD and FASN (0.907; P<0.001), SCD and SREBPF1 (0.628; P<0.001), FASN and SREBPF1 (0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Antioxidant status of colostrum is important for maternal physiology and offspring health 35 . COX-2 and NRF2 are the most related genes with the oxidative status of tissues and biological liquids and have tended to be upregulation in response to immunological activity 36,37 . It has been reported that NRF2 increases by triggering TLR2 in leukocytes and oxidative stress may decrease by overexpressing TLR2 in goats 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant status of colostrum is important for maternal physiology and offspring health 35 . COX-2 and NRF2 are the most related genes with the oxidative status of tissues and biological liquids and have tended to be upregulation in response to immunological activity 36,37 . It has been reported that NRF2 increases by triggering TLR2 in leukocytes and oxidative stress may decrease by overexpressing TLR2 in goats 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant status of colostrum is important for maternal physiology and offspring health 44 . COX-2 and NRF2 are the most related genes with the oxidative status of tissues and biological liquids and have tended to be upregulation in response to immunological activity 45 , 46 . It has been reported that NRF2 increases by triggering TLR2 in leukocytes and oxidative stress may decrease by overexpressing TLR2 in goats 47 .…”
Section: Discussionmentioning
confidence: 99%